The effect of magnetic nanoparticles on neuronal differentiation of induced pluripotent stem cell-derived neural precursors - Jiráková, Klára; Šeneklová, Monika; Jirák, Daniel; Turnovcová, Karolína; Vosmanská, Magda; Babič, Michal; Horák, Daniel; Veverka, Pavel; Jendelová, Pavla (International journal of nanomedicine, 2016)
INTRODUCTION: Magnetic resonance (MR) imaging is suitable for noninvasive long-term tracking. We labeled human induced pluripotent stem cell-derived neural precursors (iPSC-NPs) with two types of iron-based nanoparticles, silica-coated cobalt zinc ferrite nanoparticles (CZF) and poly-l-lysine-coated iron oxide superparamagnetic nanoparticles (PLL-coated γ-Fe2O3) and studied their effect on proliferation and neuronal differentiation. MATERIALS AND METHODS: We investigated the effect of these two contrast agents on neural precursor cell proliferation and differentiation capability. We further defined the intracellular localization and labeling efficiency and analyzed labeled cells by MR. RESULTS: Cell proliferation was not affected by PLL-coated γ-Fe2O3 but was slowed down in cells labeled with CZF. Labeling efficiency, iron content and relaxation rates measured by MR were lower in cells labeled with CZF when compared to PLL-coated γ-Fe2O3. Cytoplasmic localization of both types of nanoparticles was confirmed by transmission electron microscopy. Flow cytometry and immunocytochemical analysis of specific markers expressed during neuronal differentiation did not show any significant differences between unlabeled cells or cells labeled with both magnetic nanoparticles. CONCLUSION: Our results show that cells labeled with PLL-coated γ-Fe2O3 are suitable for MR detection, did not affect the differentiation potential of iPSC-NPs and are suitable for in vivo cell therapies in experimental models of central nervous system disorders.
Keywords: buněčná diferenciace; lysin; Microscopy, Electron, Transmission; Neurons; proliferace buněk; Fetus; Cell Differentiation; Induced Pluripotent Stem Cells; Magnetite Nanoparticles; průtoková cytometrie; magnetické nanočástice; Cells, Cultured; Female; Humans; Fibroblasts; magnetická rezonanční tomografie; fibroblasty; lidé; kontrastní látky; kvantitativní polymerázová řetězová reakce; ženské pohlaví; Real-Time Polymerase Chain Reaction; imunoenzymatické techniky; Cell Proliferation; plod; Lung; Flow Cytometry; Magnetic Resonance Imaging; Contrast Media; neurony; indukované pluripotentní kmenové buňky; plíce; Lysine; kultivované buňky; transmisní elektronová mikroskopie; Immunoenzyme Techniques